2022
DOI: 10.1136/bmj-2022-072623
|View full text |Cite
|
Sign up to set email alerts
|

Rivaroxaban treatment for six weeks versus three months in patients with symptomatic isolated distal deep vein thrombosis: randomised controlled trial

Abstract: Objective To compare two different treatment durations of rivaroxaban in patients with symptomatic isolated distal deep vein thrombosis (DVT). Design Randomised, double blind, placebo controlled clinical trial. Setting 28 outpatient clinics specialising in venous thromboembolism. Participants 402 adults (≥18 years) with symptomatic isolated distal DVT. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
(57 reference statements)
0
16
0
Order By: Relevance
“…11 Another recent randomized clinical trial, the RIDTS study (Rivaroxaban Treatment for Six Weeks Versus Three Months), showed that rivaroxaban administered for 6 additional weeks in patients with isolated distal DVT who had an uneventful 6-week treatment course reduced the risk of recurrent VTE. 13 However, these studies excluded patients with active cancer, who were considered at high risk for thrombotic events. The American College of Chest Physicians 2021 guidelines weakly recommend that patients with isolated distal DVT with active cancer should receive anticoagulation therapy, and the anticoagulation strategy should be the same as that for patients with proximal DVT, which means that an extended duration of anticoagulation therapy might be recommended.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Another recent randomized clinical trial, the RIDTS study (Rivaroxaban Treatment for Six Weeks Versus Three Months), showed that rivaroxaban administered for 6 additional weeks in patients with isolated distal DVT who had an uneventful 6-week treatment course reduced the risk of recurrent VTE. 13 However, these studies excluded patients with active cancer, who were considered at high risk for thrombotic events. The American College of Chest Physicians 2021 guidelines weakly recommend that patients with isolated distal DVT with active cancer should receive anticoagulation therapy, and the anticoagulation strategy should be the same as that for patients with proximal DVT, which means that an extended duration of anticoagulation therapy might be recommended.…”
Section: Discussionmentioning
confidence: 99%
“…6 A previous study reported that approximately 4.6% of patients with cancer had distal DVT. 7 Despite the relatively high frequency of isolated distal DVT in patients with cancer, [8][9][10] previous clinical trials evaluating isolated distal DVT excluded patients with cancer, [11][12][13] which resulted in a huge uncertainty of the optimal management strategies including the duration of the anticoagulation therapy and subtypes of distal DVT. 14 However, a previous observational study showed that patients with cancer with isolated distal DVT were usually treated with a limited duration period of anticoagulation therapy and were at a relatively high risk of recurrent VTE after discontinuation of the anticoagulation therapy, 15 which suggested that those patients might benefit from prolonged anticoagulation therapy.…”
Section: Yamashita Et Almentioning
confidence: 99%
“…Deep venous thrombosis (DVT) is a common venous thromboembolism that usually affects the lower extremities. The annual incidence rate is close to 1.6 per 1000 people 1 . Thrombosis usually begins in the deep vein of the leg and spreads proximally.…”
Section: Introductionmentioning
confidence: 94%
“…14 The RIDTS trial recently addressed the important question of whether anticoagulation for 3 months is superior to 6 weeks in symptomatic outpatients with acute IDDVT and no active cancer. 5 After completing uneventful 6 weeks of standard-dose rivaroxaban (15 mg twice daily), 402 subjects were randomized to receive rivaroxaban 20 mg or placebo once daily for 6 additional weeks, and followed for 2 years. 5 Recurrent VTE occurred in 11% and 19% of subjects in the rivaroxaban and placebo groups, respectively (relative risk, 0.59; 95% confidence interval, 0.36-0.95; P=0.03).…”
Section: Non-cancer-associated Iddvt: 6-week Vs 3-month Anticoagulationmentioning
confidence: 99%
“…IDDVT has long been understudied until recent times. This Editorial Focus outlines latest relevant research findings with particular attention to two recent randomized controlled studies, namely the RIDTS 5 and ONCO DVT 6 trials, and discusses how these may advance personalized management of patients with IDDVT.…”
mentioning
confidence: 99%